Meninjau Ulang Peran Kesejahteraan Spiritual terhadap Stres Akademik Mahasiswa - Pamungkas, Sukma Wisnu; Munadi, Muhammad (Paedagogie, 2026)
This study aims to analyze the influence of spiritual well-being on stress levels among seventh-semester students of the Islamic Education Study Program at UIN Raden Mas Said Surakarta. Employing an explanatory quantitative approach, the study involved 156 participants selected using proportional random sampling. Spiritual well-being was assessed using the SHALOM scale, while academic stress was measured with the Academic Stress Scale. Data were analyzed through descriptive statistics, prerequisite tests, and non-linear regression. The findings indicate that both spiritual well-being and stress levels fall within the moderate range, and there is no significant association between the two variables. The exponential regression model produced the highest coefficient of determination at 3%, though the effect remained very weak. These results suggest that spiritual well-being has not yet functioned as a primary protective factor against academic stress, highlighting the need to consider additional elements such as time management, social support, and adaptive coping strategies in campus-based interventions.